Amount and Fate of Gas and Oil Discharged at 3400 m Water Depth From a Natural Seep Site in the Southern Gulf of Mexico - Römer, Miriam; Hsu, Chieh-Wei; Loher, Markus; MacDonald, Ian R.; dos Santos Ferreira, Christian; Pape, Thomas; Mau, Susan; Bohrmann, Gerhard; Sahling, Heiko (Frontiers in Marine Science, 2019)
This multi-disciplinary study of the hydrocarbon seepage system at Tsanyao Yang Knoll in the southern Gulf of Mexico illustrates the amount and fate of hydrocarbons (mainly oil and methane) emanating from the seafloor structure and rising through a 3400 m water column. Tsanyao Yang Knoll forms part of the Campeche Knolls and was found to be one of the most active seepage structures at such an exceptional depth. Combining ship-based and AUV-based hydroacoustic mapping with direct seafloor observations and investigations, which used a TV-sled and a ROV with gas and water sampling devices provided an integrated view for the various transport pathways of hydrocarbons from the seafloor to the sea surface. In total, 32 acoustic ‘flares’, indicative of gas bubble emission sites, were detected emanating from depressions on top of the knoll. Most of the emission sites were concentrated in two depressions that comprised a main seep field. An estimated volume of 1359–4900 litres of hydrocarbons per hour are released in the form of gas bubbles, which dissolve almost entirely during their rise in the water column. However, echograms showed gas anomalies to about 500 meters below sea surface and some bubbles were seen to burst at the sea surface. Ex situ concentrations of dissolved methane were highly elevated (~30 000 nmol/L) directly above the seafloor emission site, but decreased to background concentrations (3–5 nmol/L) within the lowermost 100 m. Smaller quantities of oil also escaped from the seafloor, rose to the sea surface and generated natural oil slicks visible from the ship and in satellite images. This study shows that hydrocarbon seepage at ~3400 m water depth can be followed to the sea surface. However, most of the methane dissolves in deeper waters, whereas oil reaches the sea surface.